Design and Simulation of a Cutting Mechanism for a Millet Harvesting Machine. - Twebazibwe, Edson (Kabale University, 2024)
This report presented the key aspects and findings of a study focused on designing a millet-cutting mechanism that utilizes the scissor mechanism. The purpose of this report is to provide a concise overview of the research conducted and the main outcomes achieved. Chapter one includes an introduction on the brief background of millet cutters, the problem to be solved, the project scope with the main objective and specific objectives, research questions, research scope, justification, significance, and limitations of the project. The intended problem to be solved in this design is that existing machines are expensive and thus have certain limitations to local farmers and the cheap ones present such as knives take ages to harvest in a small place or garden. There is a need to develop a millet cutter that enhances performance and overcomes these challenges.Chapter two entails the literature review of the present millet harvesting techniques. Chapter three talks about the methodology used to come out with a designed machine including customers’ requirements, the operating principle of the machine, and the layout of the machine in solid works. Chapter four finalizes the project design, and chapter five discusses and analyzes the results of the designed millet cutter, taking into account the size of the machine components. Various data sources and references used in this report are provided at the end of the document. The key outcome of the design is that small-scale farmers will have access to cheap, reliable, and efficient machines to aid them harvest their ready millet crops with ease. This means that they will spend less time, money, and labor compared to when harvesting using a mere knife and will save huge amounts of money that would have been spent on buying heavy machinery like reapers which are even too expensive for the local farmers. This scissor mechanism-based machine will bridge the gap existing between heavy machinery like reapers and combine harvesters and local methods such as the use of knives and sickles to harvest finger millet. More so, this machine can harvest only millet heads and not the whole crop depending on the operator’s preference and therefore most farmers who are not livestock farmers will be relieved of the burden of sorting the millet heads from stalks as has been the case after harvesting. With this machine, the farmers do not need the sorting and so can immediately take harvest for sun drying.